2021
DOI: 10.1159/000515470
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Skin Photoallergy Risk in Cosmetics Containing Herbal Extract Ingredients

Abstract: <b><i>Background/Objective:</i></b> In recent years, herbal extracts are becoming increasingly popular ingredients added in cosmetics; however, the assessment of their potential adverse effects on the skin remains unclear. As <i>Coptis</i>, <i>Phellodendron amurense</i>, curcumin, and shikonin are herbs currently used in cosmetic ingredients, the aim of this study was to assess their skin photoallergy (PA) potential and the concentrations at which they could safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Other potential photoallergens are natural products which are more difficult to evaluate using in vitro methodologies. There are some studies involving volunteers [62], but this kind of study presents ethical concerns, as pointed by the Scientific Committee of Consumer Safety of the European Union [63]. Photopatch tests should be performed only for diagnostic purposes not for the safety evaluation of cosmetic ingredients.…”
Section: Pérez-ruíz Et Al 2017 [41]mentioning
confidence: 99%
“…Other potential photoallergens are natural products which are more difficult to evaluate using in vitro methodologies. There are some studies involving volunteers [62], but this kind of study presents ethical concerns, as pointed by the Scientific Committee of Consumer Safety of the European Union [63]. Photopatch tests should be performed only for diagnostic purposes not for the safety evaluation of cosmetic ingredients.…”
Section: Pérez-ruíz Et Al 2017 [41]mentioning
confidence: 99%
“…A recent study demonstrated involvement of radical intermediates formed from hydroperoxides of citronellol in protein haptenation . Topical nonsteroidal anti-inflammatory drugs (NSAIDs) and organic UV light absorbers in sunscreens are clinically the most relevant photoactivated small molecule allergens, but the list is extended to numerous antibiotics, antifungal agents, agrochemicals, food additives, plant extracts, and fragrances. …”
Section: Understanding Protein Haptenationmentioning
confidence: 99%
“…In the research, 5, 10, 25, and 50% concentrations were used in the patch test system for 48 h. The test was applied to 33 healthy Chinese subjects, while the photo patch test was administered to 206 subjects, whose skin was characterized by photosensitivity. It was indicated that a 5% concentration of shikonin can be applied in cosmetics products as a safe ingredient not causing photosensitive or contact allergic reactions on the skin [ 74 ]. Another property of shikonin is the ability to stimulate the growth of human keratinocytes and dermal fibroblasts, which was confirmed by MTS assay allowing for cell growth measurements; thus, shikonin can promote wound healing.…”
Section: Shikonin For Cosmetic Applicationsmentioning
confidence: 99%